Komponen Intellectual Capital Sebagai Prediktor Nilai Perusahaan Melalui Reputasi - Jao, Robert; Ng, Suwandi; Holly, Anthony; Edo, Theobaldus Juniardy Edo (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2024)
The aim of this study is to investigate the impact of intellectual capital components on firm value mediated by firm reputation. This study uses secondary data, namely the annual report and Corporate Image Index (CII) published by Frontier Consulting Group. The population in this study are banking companies listed on the Indonesia Stock Exchange which have a CII score consecutively during 2013-2021 period. This study uses path analysis. The results of this study indicate that human capital has a positive and significant influence on firm reputation and firm value. Capital employed has a positive but not significant effect on firm reputation and firm value. Structural capital has a negative but not significant effect on firm reputation. Structural capital has a positive but not significant effect on firm value. Firm reputation has a positive and significant influence on firm value. Firm reputation mediates the influence of human capital on firm value with partial mediation type. Firm reputation does not succeed in mediating the influence of capital employed and structural capital on firm value.